The relationship between cyberbullying victimization and cyberbullying perpetration: The role of social responsibility - Zhan, Jun; Yang, Yue; Lian, Rong (Frontiers in Psychiatry, 2022)
Previous studies have found some influencing factors of cyberbullying. However, little is known about how cyberbullying victimization and social responsibility influence college students’ cyberbullying perpetration or about the mediating and moderating mechanisms underlying these relationships. Social responsibility involves not only individuals’ deep cognition and special emotional identification of social responsibility but also their firm attitude and responsible actions. The purpose of this study is to investigate the relationship between college students' cyberbullying victimization and cyberbullying perpetration and whether this relationship is moderated by social responsibility. The study sample consisted of 1016 Chinese college students (425 males and 591 females) ranging in age from 19 to 25 (mean age 22). All participants completed questionnaires on cyberbullying victimization, cyberbullying perpetration and social responsibility. The results indicated that cyberbullying victimization is positively related to cyberbullying perpetration and that this relationship is mediated by social responsibility. This study highlights the harmful impact of cyberbullying victimization on college students, more notably, the underlying mechanisms between cyberbullying victimization and cyberbullying perpetration are explored, revealing that social responsibility can reduce the promoting effect of cyberbullying victimization on cyberbullying perpetration.